Pengaruh Budaya Organisasi terhadap Kepuasaan Kerja Karyawan - Muhammad Rachman Mulyandi; Mario Anthony Rusly (Jurnal Syntax Transformation, 2021)
This research aims to determine UMKM Harchi Studio : Architecture & Interior Design organizational culture to employee job satisfaction on UMKM Harchi Studio : Architecture & Interior Design employee. Organizational culture as independent variable using Cameron & Quinn theory’s that divide culture into four types. Each organization will always had all this type but there always be the one above all. Job satisfaction as independent variable using Weiss et al. theory that divide job satisfaction into 20 job satisfaction factors. Methodology research using a qualitative analysis which is traditional literature review. The result shows that organizational culture have significantly influencing employee job satisfaction